The effect of acidification on hydrogen uptake and corrosion resistance of advanced high-strength steels - Maryna Taryba; Afonso Cruz; Nikola Macháčková; Fatima Montemor; Tomáš Prošek; Dominique Thierry (Journal of Materials Research and Technology)
High strength steels are susceptible to hydrogen embrittlement that may contribute to degradation of steel parts and structural failure. The correlation between corrosion-induced hydrogen entry and electrochemical behavior of galvanized advanced high-strength steel (Press Hardened Steel and Complex Phase Steel) was studied in neutral and acidified (pH 3) 0.05 M NaCl by combination of conventional and localized electrochemical techniques with zero resistance ammeter technique and thermal desorption analysis. Hydrogen entry increased in acidic environment due to lowered galvanic protection of both coatings. In Press Hardened Steel, it was additionally aggravated by pitting of insufficiently galvanically protected steel.